Notorious Woman : The Celebrated Case of Myra Clark Gaines - Alexander, Elizabeth Urban, 1947- (Book collections on Project MUSE., 2001)
The legal crusade of Myra Clark Gaines (1804?-1885) has all the trappings of classic melodrama - a lost heir, a missing will, an illicit relationship, a questionable marriage, a bigamous husband, and a murder. For a half century the daughter of New Orleans millionaire Daniel Clark struggled to justify her claim to his enormous fortune in a case that captivated the nineteenth-century public. Elizabeth Urban Alexander taps voluminous court records and letters to unravel the twists and turns of Gaines's litigation and reveal the truth behind the mysterious saga of this notorious woman. Myra, the d.